Effect of Recreational Futsal on Body Composition in Passive Football Players - Arben Maliqi; Blerim Sylejmani; Nazim Myrtaj (Physical Education Theory and Methodology, 2022)
The purpose of this study was to evaluate the impact of recreational futsal on passive middle-aged footballers in body composition.